Cyclometalated Ruthenium(II) Complex as a Versatile Catalyst for Living/Controlled Radical Polymerization of Hydrophobic and Hydrophilic Monomers. Issue 1 (15th April 2013) - Alfredo, Nelson Vargas; Aguilar‐Lugo, Carla; Gonzalez, Ortencia Diaz; Le Lagadec, Ronan; Alexandrova, Larissa
Abstract: Cyclometalated complex, cis ‐[Ru(phpy)(phen)(MeCN)2 ]PF6, bearing strongly bound ligands (phpy = 2‐phenylpyridine, phen = 1, 10‐ phenantroline) and relatively labile (MeCN) ligands, in conjunction with ethyl 2‐bromoisobutyrate (EB i B), was used for radical polymerization of three hydrophobic, styrene (St), methyl methacrylate (MMA), n ‐butyl acrylate (BA), and one hydrophilic, 2‐hydroxyethyl methacrylate (HEMA), monomers. The polymerizations were fast and reasonably controlled; the molecular weights increased with conversion and were close to the calculated values. The best control was achieved in polymerization of St. The complex was able to mediate this polymerization with acceptable rate and level of control even at a monomer/catalyst ratio of 2000. The living character of the polymerizations was confirmed by chain extension experiments; the degree of polymer "livingness" was less for PMMA than for PSt. Because of ionic nature, the complex was well soluble in MeOH and thus catalyzed polymerization of HEMA under homogeneous conditions at 50 °C.